Compensatory Social Networking Site Use, Family Support, and Depression Among College Freshman: Three-Wave Panel Study - Zhou, Mingjie; Li, Fugui; Wang, Yanhong; Chen, Shuang; Wang, Kexin (JMIR Publications, 2020)
BackgroundFreshmen were found to use social networking sites (SNS) as a useful medium to effectively adjust to college life, which hints at a tendency to resort to SNS for social compensation. However, the compensatory use of SNS is usually problematic. ObjectiveThis study explores why a subgroup of freshmen developed depressive symptoms while socially adjusting to college by investigating the antecedent role of introversion, the explanatory role of compensatory use of SNS, and the protective role of perceived family support. The study is among the first to point out the relevance of the compensatory use of SNS in explaining the indirect association between introversion and depression with a longitudinal design. MethodsA 3-wave panel sample of freshmen (N=1137) is used to examine the moderated mediation model. ResultsWe found that introversion at Wave 1 positively predicted compensatory use of SNS at Wave 2 and subsequently increased depression at Wave 3 (unstandardized B=0.07, SE 0.02, P<.001, 95% CI 0.04-0.10; unstandardized B=0.09, SE 0.01, P<.001, 95% CI 0.06-0.12). The moderated mediation model further examined the buffering role of perceived family support within the link between introversion and compensatory SNS use (index=0.0031, SE 0.0015, 95% CI 0.0003-0.0062). Unexpectedly, we found that family support in Wave 1 decreased compensatory SNS use for less introverted freshmen in Wave 2 and further decreased depression in Wave 3. ConclusionsUnexpectedly, our findings uncover an enhancing effect, rather than a buffering effect, of family support by embedding its effect within the relationship between introversion and compensatory SNS use. Appreciating the differences in the casual pathways for freshmen with different levels of introversion clarifies how SNS affect young adults' lives.